Body composition of physically active women aged over 60 - Héctor Antonio Herrera Mogollón; Rosa Armenia Hernández Hernánde; Alba Luz Beltrán Ramírez (Universidade Federal de Santa Catarina, 2007)
With the objective of analyzing the body composition of physical active seniors: 116 women enrolled on the Program of Integrated Care for the older Adult in the Municipality of Chacao, Venezuela, were studied. Anthropometric variables were measured. Comparisons between variables revealed no statistical differences, with the exception of suprailiac skinfolds (p <0,05). Results indicated that most of the mean values were lower in the oldest group, with the exception of height, which was greater. The waist/hip ratio remained constant. More than 50% of women exhibited good nutritional status with appropriate body mass index. Cases of energy malnutrition were observed (defi ciencies and excesses), with overweight prevailing at around 20%. Waist circumference and the waist/hip ratio indicated that around 55% of the sample exhibited a high risk of developing chronic non-infectious illnesses. Comparisons with other population samples indicated greater similarity with those in their environment (Venezuelan and Mexican samples) and with Italian and Australian women, and distant from the American pattern, with minor values of the variables compared.